Sensory Characteristics Of Pinogu Coffee From Bone Bolango Gorontalo - Susilo, Bambang; Ciptadi, Gatot; Kurniawan, Syahrul; Fibrianto, Kiki; Samudra, Rizki Putra; Wulandari, Eka Shinta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
Pinogu coffee is a superior coffee from the Gorontalo region. Pinogu coffee is a type of robusta coffee. From the results of the research conducted, this Pinogu coffee has sensory characteristics that tend to be bitter (taste and aftertaste) with the aroma of smoke and wood, followed by a burnt and roasted aroma and a slightly thick body or texture that coats the oral cavity. As for the chemical characteristics, ground Pinogu coffee contains a water content of 2.51%, caffeine content of 1.99%, and copper content of 13.86 mg/kg, for steeping the coffee contains a caffeine content of 0.06% and copper content of 0,39 mg/kg.